Case report: Self-expanding transcatheter valve implantation (Acurate Neo 2) in a very small native aortic annulus - Medda, Massimo; Casilli, Francesco; Bande, Marta; Tespili, Maurizio; Donatelli, Francesco (Frontiers in Cardiovascular Medicine, 2023)
Transcatheter aortic valve replacement (TAVR) is a treatment of choice in patients with symptomatic severe aortic valve stenosis (AS) and intermediate-to-high surgical risk. The presence of a small aortic annulus (SAA) has been associated with a higher incidence of prosthesis–patient mismatch (PPM) when surgical aortic valve replacement (sAVR) is performed. TAVR might be a treatment option offering better hemodynamics with a lower incidence of PPM. When a severe AS with a SAA is treated, TAVR-related risk as the coronary obstruction and the annulus rupture, must be also prevented. We present a case of a TAVR in a very small aortic annulus; to our knowledge, this is the smallest native aortic annulus treated percutaneously in a tricuspid stenotic aortic valve with a Self-Expanding Transcatheter Heart Valve (THV) Acurate Neo 2.